2020
DOI: 10.1371/journal.pntd.0008335
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus dysregulates human Sertoli cell proteins involved in spermatogenesis with little effect on tight junctions

Abstract: Zika virus (ZIKV), a neglected tropical disease until its re-emergence in 2007, causes microcephaly in infants and Guillain-Barré syndrome in adults. Its re-emergence and spread to more than 80 countries led the World Health Organization in 2016 to declare a Public Health Emergency. ZIKV is mainly transmitted by mosquitos, but can persist in infected human male semen for prolonged periods and may be sexually transmitted. Testicular Sertoli cells support ZIKV replication and may be a reservoir for persistent ZI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 103 publications
(125 reference statements)
4
23
0
Order By: Relevance
“…However, it is also important to note that, in contrast to SC, ZIKV-infected NPC cultures undergo different degrees of cell death and experience impairments in cellular growth depending on their state of differentiation (Wells et al, 2016;Wen et al, 2017), and thus it is plausible that the antiviral responses in NPC may be similarly affected in this regard. In contrast to our LC-MS/MS proteomics analysis, Rashid and colleagues recently employed the SOMAscan aptamer-based multiplexed proteomics approach, that targets a predefined set of proteins, to characterize proteins dysregulated by ZIKV in SC (Rashid et al, 2020). However, although their study reported altered levels related to cell growth, death, and survival in infected SC (Rashid et al, 2020), they could not detect changes in ISGencoded proteins since they were not included in the predefined set of protein targets of the SOMAscan aptamer-based platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also important to note that, in contrast to SC, ZIKV-infected NPC cultures undergo different degrees of cell death and experience impairments in cellular growth depending on their state of differentiation (Wells et al, 2016;Wen et al, 2017), and thus it is plausible that the antiviral responses in NPC may be similarly affected in this regard. In contrast to our LC-MS/MS proteomics analysis, Rashid and colleagues recently employed the SOMAscan aptamer-based multiplexed proteomics approach, that targets a predefined set of proteins, to characterize proteins dysregulated by ZIKV in SC (Rashid et al, 2020). However, although their study reported altered levels related to cell growth, death, and survival in infected SC (Rashid et al, 2020), they could not detect changes in ISGencoded proteins since they were not included in the predefined set of protein targets of the SOMAscan aptamer-based platform.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our LC-MS/MS proteomics analysis, Rashid and colleagues recently employed the SOMAscan aptamer-based multiplexed proteomics approach, that targets a predefined set of proteins, to characterize proteins dysregulated by ZIKV in SC (Rashid et al, 2020). However, although their study reported altered levels related to cell growth, death, and survival in infected SC (Rashid et al, 2020), they could not detect changes in ISGencoded proteins since they were not included in the predefined set of protein targets of the SOMAscan aptamer-based platform.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 446 host proteins were significantly dysregulated at any time point, and 71 were dysregulated > 1.375-fold ( Table 1 ). The majority of dysregulated proteins were significantly upregulated at 12 hpi, irrespective of the fold-change cut-off used ( Table 1 ), a pattern that was not reflected by our previous analyses of ZIKV-infected Vero [ 15 ], U-251 astrocytoma [ 16 ] or Sertoli cells [ 17 ]. Bioinformatic analysis using Ingenuity Pathway analysis (IPA) predicted several pathways that were activated and inhibited by ZIKV infection.…”
Section: Introductionmentioning
confidence: 81%
“…We have been examining proteomic alterations induced by ZIKV in various cell types, including monkey kidney Vero [ 15 ], human U-251 astrocytoma [ 16 ] and human Sertoli [ 17 ]. Most protein dysregulation occurred at 48 hpi or later in these other cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have pointed out the importance of microRNA (miRNA), including miR-9, during ZIKV infection, leading to apoptosis-associated microcephaly, reduced numbers of NPCs, and newly formed neurons in embryonic mouse cortex [ 13 , 14 , 15 , 16 ]. ZIKV infection in neuronal stem cells also upregulates miR-124-3p, which has been predicted to be involved in microcephaly [ 17 ].…”
Section: Introductionmentioning
confidence: 99%